Dust diseases and the legacy of corporate manipulation of science and law - Egilman, David (Maney Publishing, 2014)
BACKGROUND: The dust diseases silicosis and asbestosis were the first occupational diseases to have widespread impact on workers. Knowledge that asbestos and silica were hazardous to health became public several decades after the industry knew of the health concerns. This delay was largely influenced by the interests of Metropolitan Life Insurance Company (MetLife) and other asbestos mining and product manufacturing companies. OBJECTIVES: To understand the ongoing corporate influence on the science and politics of asbestos and silica exposure, including litigation defense strategies related to historical manipulation of science. METHODS: We examined previously secret corporate documents, depositions and trial testimony produced in litigation; as well as published literature. RESULTS: Our analysis indicates that companies that used and produced asbestos have continued and intensified their efforts to alter the asbestos–cancer literature and utilize dust-exposure standards to avoid liability and regulation. Organizations of asbestos product manufacturers delayed the reduction of permissible asbestos exposures by covering up the link between asbestos and cancer. Once the decline of the asbestos industry in the US became inevitable, the companies and their lawyers designed the state of the art (SOA) defense to protect themselves in litigation and to maintain sales to developing countries. CONCLUSIONS: Asbestos product companies would like the public to believe that there was a legitimate debate surrounding the dangers of asbestos during the twentieth century, particularly regarding the link to cancer, which delayed adequate regulation. The asbestos–cancer link was not a legitimate contestation of science; rather the companies directly manipulated the scientific literature. There is evidence that industry manipulation of scientific literature remains a continuing problem today, resulting in inadequate regulation and compensation and perpetuating otherwise preventable worker and consumer injuries and deaths.